DRIVERS OF NEW VENTURE DIGITALIZATION AMONG MALAYSIAN SMES: A CONCEPTUAL MODEL - Chin, Tay Lee; Amy, Yeo Chu May; Tan, Houng Chien; Abina, Babatunde Musiliu (International Journal of Application on Economics and Business, 2023)
This study is an extension of previous studies focusing on new venture digitalization. It examines the influence of the drivers of new venture digitalization on small and medium enterprises (SMEs). Using a systematic literature review, the study developed a conceptual model to examine the drivers of new venture digitalization among Malaysian SMEs. The findings reveal the extent to which organizational factors such as size, ownership and international experience of firms can influence Malaysian SMEs’ new venture digitalization. It also indicates that individual and environment factors such as age, gender, and education; government intervention, competitors and customers pressure, Covid-19 health crisis, blockchain technology and fast broadband access have the potential to drive Malaysian SMEs’ new venture digitalization. The study contributes to models on new venture digitalization and provides a better understanding of general and country specific factors that drives the utilization of digitalization in new ventures.